Naglasni problemi stare in moderne grščine - Kavčič, Jerneja (Keria (Ljubljana), 2000)
The subject of the article are the accentual features of ancient and modern Greek. The first part discusses the problems of the position of the Greek accent at the earliest stages of development and the accentual rules of Ionic-Attic, Lesbic and Doric dialect. The second and the third part present the questions of the phonetics of the ancient Greek accent and the process in which the modern Greek accent appeared.
Keywords: grščina; lingvistika; naglas; stara grščina